(untitled) (Research, Society and Development, 2020)
The palm had its origin in North and South America and has great potential for semi-arid regions, widely cultivated in Northeast Brazil, for tolerating long periods of drought. Because it is a cactacea its physiology provides greater efficiency in the use of water. The stem is succulent with an estimated relevant nutritional value to be used in the human diet. The objective was to discuss the most consumed palm genera, their bioactive compounds and information on their metabolism. A bibliographic survey was carried out on research platforms where 57 articles were selected to be used as a database. The content of bioactive compounds, the aroma, the color, the texture and the taste can be changed according to the enzymatic activity, mainly the phenylalanine ammonia lyase.